Experimental and numerical study on the hydrodynamic behaviors of mooring line failure on a net cage in irregular waves and currents - Tang, Hung-Jie; Yang, Ray-Yeng; Yao, Hao-Cheng (Frontiers in Marine Science, 2023)
The failure of mooring lines in net cages could lead to the death or escape of farmed fish, which causes huge economic losses and immeasurable ecological impacts. Therefore, it is very important to ensure the safety of the cage mooring system in practical applications. This study experimentally and numerically investigates the hydrodynamic behaviors of the mooring line failure on a net cage in irregular waves and currents. For the model test, a 1:25 scaled net cage model with eight-point mooring is installed in a wave tank. The two load cells in its upstream mooring lines and a gyroscope on its floating collar are used to measure the mooring force and the rotational motions, respectively. A cutting device equipped with a pneumatic cylinder and a blade is used to cut the line. A self-developed numerical model is specifically established for the model test for cross-validation. Both experimental and numerical results are analyzed and compared in the time and frequency domains. The results show that the mooring load in the remaining line significantly increases as one of the upstream mooring lines is disconnected. Meanwhile, a significant yaw rotation of the floating collar is observed. The results indicate that the maximum tension, drift displacement, and rotational angles significantly increase as the current velocity increases.